ACQUISITION OF JEWISH CULTURAL HERITAGE OF LATGALE IN REGIONAL EDUCATIONAL ESTABLISHMENTS: DISCOURSE OF CULTURAL MEMORY - Senkāne, Olga; Laganovska, Karīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the context of culture and history discourse and sociological analysis the interdisciplinary research reveals the significance of Jewish cultural heritage in the multinational Latgale region. Therefore, there are described topical tools in the research and preservation of Jewish cultural values and evaluated the necessity for acquisition of this culture at regional educational establishments. Prior to holocaust the ethnical group of Jews was one of the largest minorities in Latgale and had significant impact on the socio-economic and cultural development of the region. As a result of the research, it was found out that pupils and students possess knowledge about holocaust, but they have no clue about the life of this minority in Latgale before World War II and nowadays. In order to solve the problem the authors of the article offer to integrate the respective cultural and historical material into the interdisciplinary link because the tool forming memory culture are the contemporary realia – museum exhibits, photos, exhibitions, cultural and historical monuments, former Jewish squares and streets, architectonics of preserved houses, etc. RHEI REGI has created a virtual museum “Jews in Latgale” as an interactive tool offering teachers, museum staff and other interested persons video films, witnessing interviews and other materials.